Effect of exhaustive exercise on the angular pedaling pattern: A preliminary study - Matheus Joner Wiest; Felipe Pivetta Carpes; Mateus Rossato; Carlos Bolli Mota (Universidade Federal de Santa Catarina, 2009)
Considering biomechanical aspects such as kinematics, fatigue can be characterized as a loss of efficiency in maintaining a movement pattern, such as pedaling technique, during exercise. The objective of this preliminary study was to investigate the effects of 1-h exhaustive cycling exercise at intensity of 80% VO2max on pedaling technique. The pedaling technique was evaluated in four skilled mountain-bike cyclists by 2D kinematics. The main hypothesis of this study was that angular changes in response to fatigue would occur mainly in the ankle joint. After achievement of maximal oxygen uptake (VO2max), the cyclists were submitted to a submaximal protocol at intensity corresponding to 80% VO2max for 1 h. The cyclists were filmed throughout 10 complete consecutive crank cycles at intervals of 10 min. Images were acquired from the right lower limb and the hip, knee and ankle joint angles were measured after kinematic processing. The Shapiro-Wilk test, ANOVA and post-hoc Tukey HSD test were used for statistical analysis, with the level of significance set at 0.05. Statistical analysis showed a significant difference only for ankle kinematics after 40 min of exercise, with an increase in the range of motion from 20° at the beginning of exercise to 35° at the end of exercise. This result confirms the hypothesis proposed and suggests that only the ankle joint was affected by the exercise. The characteristics of ankle movement suggest that this joint plays a compensatory role in an attempt to maintain the pedaling technique and to sustain the exercise workload.